Managing cervical cancer in Nepal: Need of consensual guideline - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2010)
The purpose of this review is to bridge the pattern of intervention in optimal and sub-optimal facility level. Several guidelines for the screening and treatment of cervical cancer are reviewed. Routine screening is found grossly lacking and non existent outside major health institution. Only nominal data and intervention efforts found published. There are three prongs of intervention level namely prevention/screening, treatment and palliation together. Pap smear test is the standard screening tool wherever the cyto-diagnostic facility exists. Visual Inspection with Acetic acid and Lugol's Iodine will be the feasible alternative at low resource setting. Primary surgical treatment for early cervical cancer is the best option. Likewise chemo-radiation with or without surgery will be the alternative option. Need of at least an operational guideline in each institution is realized at this moment as a recommendation. Key words: Cervical intraepithelial neoplasia (CIN); colposcopy; Pap smear (Papanicolou stain); radical hysterectomy; visual inspection with acetic acid (VIA). DOI: 10.3126/njog.v4i1.3324 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 3-10